2007
DOI: 10.1007/s10310-006-0243-6
|View full text |Cite
|
Sign up to set email alerts
|

Line thinning fosters the abundance and diversity of understory Hymenoptera (Insecta) in Japanese cedar (Cryptomeria japonicaD. Don) plantations

Abstract: Line thinning fosters the abundance and diversity of understory Hymenoptera (Insecta) in Japanese cedar (Cryptomeria japonica D. Don) plantations Abstract We investigated the effects of line thinning on the abundance of Hymenoptera in two Japanese cedar plantations in northern Hyogo Prefecture, central Japan, in order to evaluate the effectiveness of this silvicultural treatment for ecosystem management. Line thinning is a silvicultural treatment practiced in Japan, where linear stand sections are cut (25%-35%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…By creating heterogeneous understory conditions, line thinning increased understory plant biomass, which in turn contributed to enhancing arthropod diversity (Maleque et al 2007). Our results suggested that restoration of ecological processes, such as food-web interactions (pollination, predation, herbivory, decomposition, parasitism, etc.)…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…By creating heterogeneous understory conditions, line thinning increased understory plant biomass, which in turn contributed to enhancing arthropod diversity (Maleque et al 2007). Our results suggested that restoration of ecological processes, such as food-web interactions (pollination, predation, herbivory, decomposition, parasitism, etc.)…”
Section: Discussionmentioning
confidence: 98%
“…The control plot (20 · 30 m 2 ) was established in an adjacent unthinned stand on the same slope. Maleque et al (2007) give a detailed description of the study site and research plots. Grimaldi and Engel (2005) Sampling, identification and grouping of Coleoptera…”
Section: Treatment Applicationsmentioning
confidence: 99%
“…Line-thinned plots support higher biomass and species richness of understory vegetation and corresponding insect abundance in Cryptomeria plantations in Japan (Maleque et al, 2006b(Maleque et al, , 2007aIshii et al, 2008). Ohsawa (2004) showed that species richness of cerambycid beetles increased in selectively thinned larch plantations (Larix kaempferi) compared to unthinned plantations in Japan.…”
Section: Use Of Bioindicators In Forest Man-agementmentioning
confidence: 90%
“…Selective cutting, line thinning, and green tree retention harvesting have been reported as ecologically friendly silvicultural techniques (Phillips et al, 2006;Jacobs et al, 2007;Maleque et al, 2007a). Line-thinned plots support higher biomass and species richness of understory vegetation and corresponding insect abundance in Cryptomeria plantations in Japan (Maleque et al, 2006b(Maleque et al, , 2007aIshii et al, 2008).…”
Section: Use Of Bioindicators In Forest Man-agementmentioning
confidence: 98%
“…The positive impacts of surrounding landscape patterns on the abundance and diversity of Coleoptera and Hymenoptera have been discussed in previous papers (Maleque et al 2006b(Maleque et al , 2007a. Other studies have also discussed the similar importance of largescale landscape patterns to biodiversity conservation in managed forests (Kerr 1999;Sakai et al 2006).…”
Section: Discussionmentioning
confidence: 91%